Core bead chromatography for preparation of highly pure, infectious respiratory syncytial virus in the negative purification mode. Issue 32 (12th July 2016) - Mundle, Sophia T.; Kishko, Michael; Groppo, Rachel; DiNapoli, Joshua; Hamberger, John; McNeil, Bryan; Kleanthous, Harry; Parrington, Mark; Zhang, Linong; Anderson, Stephen F.
Highlights: A purification procedure for respiratory syncytial virus is described. Purification is achieved by core bead chromatography followed by tangential flow filtration. The purification scheme results in ∼60% recovery of infectious virus titer. Purified RSV LAV is immunogenic and protective in vivo . Purified virus is 50–200-fold more pure with respect to cellular DNA and protein than the raw feed stream. Abstract: Respiratory syncytial virus (RSV) is an important human pathogen, and is the most frequent viral cause of severe respiratory disease in infants. In addition, it is increasingly being recognized as an important cause of respiratory disease in the elderly and immunocompromised. Although a passive prophylactic treatment does exist for high-risk neonates and children, the overall disease burden warrants the development of a safe and effective prophylactic vaccine for use in otherwise healthy newborns and children. RSV is known to be an extremely labile virus, prone to aggregation and loss of infectious titer during virus handling and preparation procedures. To date infective RSV virions have been prepared by methods which are not readily scalable, such as density gradient ultracentrifugation. In this study we describe a scalable, chromatography-based purification procedure for preparation of highly pure, infectious RSV. The purification scheme is based on core bead technology and hollow fiber tangential flow filtration (TFF) and results in a ∼60% recovery of infectious virus titer. This method can be used to prepare highly purified wild type or live-attenuated vaccine strain viruses with titers as high as 1 × 10 8 plaque forming units per mL. A live-attenuated RSV vaccine prepared by this method was found to be immunogenic and protective in vivo, and its purity was 50–200-fold greater with respect to host cell dsDNA and Vero host cell proteins, than the raw feed stream. The results presented here can be considered a starting point for downstream process development of a live-attenuated vaccine approach for prevention of disease by RSV.